Juozas Tumas-Vaižgantas and the Society for Making Lithuania Beautiful - Smilingytė-Žeimienė, Skirmantė (Colloquia, 2020)
The article presents activities of the Society for Making Lithuania Beautiful established in Lithuania in 1921. The vision and actions of its ideologue and first chairman Juozas Tumas-Vaižgantas contributed to a more active process of memorialization in Lithuania, introducing the idea that it was necessary to build monuments as a ‘reward’ to prominent people or historical figures and fill in the vacuum created by the tsarist occupation which banned national monuments in the country. At that time, there was a great shortage of memorials, so the decision to introduce new identification marks in the form of a tree (every year, a tree with an agreed name and memorial function was planted in a special place) or of a monument was timely, as was the attempt to replant the war-torn country and beautify its surroundings. The imperative goal to make Lithuania beautiful turned into actions and traditions, such as annual visits and upkeep of historical objects, especially hill forts, tree planting and bird festivals. Tumas-Vaižgantas and the Society encouraged Lithuanians to nurture the landscape and cultural heritage objects, to create signs significant for the nation, and at the same time, spaces of local memory. In this way, the romanticized concept of statehood was introduced through visuals.
Keywords: Juozas Tumas-Vaižgantas; Society for Making Lithuania Beautiful; cultural landscape; memorialization; monuments; culture of memory